OPTIMIZATION OF EDIBLE FILM FORMULA BASED ON MAIZENA, CARRAGEENAN, AND RICE BRAN FOR HAND CANDY PACKAGING - Purwoto , Heri; Ismawanti , Ratih Dwi; Harianto, Harianto; Djafar , M. Jusuf; Putri , Widya Dwi Rukmi; Murtini , Erni Sofia (Majalah Ilmiah Pengkajian Industri, 2020)
Plastic packaging has dominated the waste, and the number is increasing every year. Candy plastic packaging waste is most often considered trivial because of its small size, so it is usually disposed of carelessly. Due to its non-biodegradable, it causes environmental pollution. Edible film packaging is an alternative to reduce the impact of candy packaging waste pollution. The purpose of this study was to obtain the optimum formula of the edible film between corn starch, carrageenan, and rice bran as a hard candy packaging with the Response Surface Methodology (RSM) Central Surface Composite Design using the Design Expert 10.0.7. The prediction data obtained is then verified and tested by t-test at a 5% reliance interval.The optimum formulation of RSM results is 3.4% of corn starch, 1.1% of carrageenan and 0.38% of rice bran with predicted response of water content of 14.51%, WVTR 61,06 g/m2/hour, viscosity of 258.8 cP, tensile strength of 107.9 kgf/cm2, elongation of 19.41%, and modulus of response young 586.28 kgf/cm2. The verification of the optimum formula had a moisture content of 14.37%, WVTR 63.34 g/m2/hour, viscosity of 244.9 cP, tensile strength of 96.9 kgf/cm2, elongation of 20.96%, and young modulus of 462.49 kgf/cm2. Key Words : Corn starch; Carrageenan; Rice bran; Formula optimization; Edible film; Hard candy Â